Exploring the links between necrotizing enterocolitis and cow's milk protein allergy in preterm infants: a narrative review - Moak, Rosemary; Boone, Neal; Eidson, Natalie; Rohrer, Allison; Engevik, Mindy; Williams, Kelli; Chetta, Katherine (Frontiers in Pediatrics, 2023)
A broad range of allergic disorders and intolerance are associated with cow's milk protein in the infant diet. Allergy and intolerance to cow's milk proteins are commonly recognized in the healthy term infant, and the prevalence cow's milk protein intolerance (CMPI) varies widely but 5 challenge confirmed studies free from selection bias ranged from 1.9%-4.9%. These disorders are classified by the presence of IgE, non-IgE or T-cell-mediated signaling. Additionally, the severity of these adverse food reactions can range from mild gastrointestinal symptoms to severe sepsis-like episodes, as in the case of food protein-induced enterocolitis syndrome (FPIES). Food protein-induced intolerance in the healthy young infant lies in stark contrast to enterocolitis that typically occurs in the preterm neonate. Necrotizing enterocolitis (NEC) is a distinct progressive disease process, usually characterized by a high mortality rate, with a risk of death from 30-50%. While its exact etiology is unclear, its main triggers include formula (cow's milk protein), hypoxia, perfusion-related issues, and unregulated inflammation in the premature intestine. The distinction between NEC and cow's milk protein intolerance is difficult to discern in some cases. In the late preterm population, infants with colitis can have both NEC and cow's milk intolerance on the differential. In infants with multiple episodes of mild NEC, cow's milk protein intolerance may be the underlying diagnosis. In this review, we compare the pathophysiological characteristics, diagnosis and treatment of disorders of cow's milk protein intolerance with the entity of preterm NEC. This review highlights similarities in both entities and may inspire future crossdisciplinary research.